MITOCHONDRIA-TARGETED ANTIOXIDANTS FOR TREATMENT OF PARKINSON’S DISEASE: PRECLINICAL AND CLINICAL OUTCOMES - Jin, Huajun (2013)
Parkinson’s disease (PD) is a progressive neurodegenerative disease in the elderly, and no cure or disease-modifying therapies exist. Several lines of evidence suggest that mitochondrial dysfunction and oxidative stress have a central role in the dopaminergic neurodegeneration of PD. In this context, mitochondria-targeted therapies that improve mitochondrial function may have great promise in the prevention and treatment of PD. In this review, we discuss the recent developments in mitochondria-targeted antioxidants and their potential beneficial effects as a therapy for ameliorating mitochondrial dysfunction in PD.